Pelaksanaan Budaya Unggul Limbah Batok Kelapa di SDN Wilangan 01 Kabupaten Nganjuk - Tahez Zaenuddin Tri Sunyoto; Retno Tri Wulandari; Goenawan Roebyanto; Tahez Zaenuddin Tri Sunyoto; Retno Tri Wulandari (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2021)
Abstract: The application of superior culture carried out in superior schools aims to achieve effective learning in schools. SDN Wilangan 1 Nganjuk Regency has a superior culture program. The program is the use of waste within the scope of the school, by utilizing unused coconut shells, it indirectly shows concern for the environment. This research uses a qualitative approach with the type of case study research. Data collection techniques used interviews, observation, and documentation studies. In analyzing this data, the researcher used several stages of qualitative data analysis, namely data reduction, data presentation, and verification. The results showed that the implementation of a superior culture of coconut shell waste at SDN Wilangan 1 Nganjuk Regency was implemented through: 1) Preparation of coconut shell waste utilization, 2) Implementation of coconut shell waste utilization activities, 3) Results of utilizing coconut shell waste, 4) Planning of cultural work programs superior, 5) Organizing work programs, 6) Implementation of work programs, 7) Evaluation of work programs. Abstrak: Penerapan budaya unggul yang dilaksanakan di sekolah unggul bertujuan untuk mencapai keefektifan pembelajaran di sekolah. SDN Wilangan 1 Kabupaten Nganjuk memiliki program budaya unggul. Program tersebut adalah pemanfaatan limbah dalam lingkup sekolah, dengan memanfaatkan batok kelapa yang tidak digunakan, hal tersebut secara tidak langsung menunjukkan kepedulian terhadap lingkungan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Teknik pengumpulan data menggunakan wawancara, observasi dan studi dokumentasi. Dalam analisis data ini, peneliti menggunakan beberapa tahap analisis data kualitatif, yaitu reduksi data, penyajian data, verifikasi. Hasil penelitian menunjukkan bahwa pelaksanaan budaya unggul limbah batok kelapa di SDN Wilangan 1 Kabupaten Nganjuk diterapkan melalui: 1) Persiapan pemanfaatan limbah batok kelapa, 2) Pelaksanaan kegiatan pemanfaatan limbah batok kelapa, 3) Hasil pemanfaatan limbah batok kelapa, 4) Perencanaan program kerja budaya unggul, 5) Pengorganisasi program kerja, 6) Pelaksanaan program kerja, 7) Evaluasi program kerja.